2022
DOI: 10.3102/0091732x221084331
|View full text |Cite
|
Sign up to set email alerts
|

Black Brilliance and Creative Problem Solving in Fugitive Spaces: Advancing the BlackCreate Framework Through a Systematic Review

Abstract: Traditional definitions and assessments of creativity often neglect to identify the complexity surrounding Black students’ brilliance, leading to lack of access and funding. Further, even when recognized, Black students are often funneled into programs that do not facilitate positive development of their racial-ethnic identity. Through our systematic review of 155 publications, we developed the BlackCreate Framework to illustrate how effective Black creative educational experiences (BCEEs) create fugitive spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…Art and storytelling should be used in the classroom to invent new futures and take action toward ensuring those futures, as they are critical elements of abolitionist teaching. As Mims et al (2022) warned, when using art, we cannot constrict Black art-making practices in rigid ways. Rather, we must invite them to engage in art-making practices that they gravitate toward.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Art and storytelling should be used in the classroom to invent new futures and take action toward ensuring those futures, as they are critical elements of abolitionist teaching. As Mims et al (2022) warned, when using art, we cannot constrict Black art-making practices in rigid ways. Rather, we must invite them to engage in art-making practices that they gravitate toward.…”
Section: Discussionmentioning
confidence: 99%
“…As an example of this work in practice, Dando et al ( 2019) studied the ReMixing Wakanda Project, where students engaged in design practices to create medallions as an artifact that detailed their personal histories and then were put together to make a collective artifact. Additionally, in a systematic review of 155 publications, Mims et al (2022) found that research and practice often confines Black creativity and neglects Black brilliance. Thus, they call for more support for fugitive spaces that center creative expression and education, particularly because many of the spaces where Black children engaged in effective creative educational experiences were outside of traditional schooling spaces (Mims et al, 2022).…”
Section: Arts Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we amplify existing scholarship on Black fugitivity in education (Givens, 2021;Mims et al, 2022;Warren & Coles, 2020), specifically soliciting future researchers to be coconspirators working in partnership with Black people (Love, 2020) to develop fugitive spaces where the rich legacy of Black people and Black resistance are celebrated rather than denigrated. Stovall and Moseley (2023) remind us that Black fugitive spaces are about more than the absence of White people or anti-Black structures.…”
Section: Black Fugitivity In Educationmentioning
confidence: 99%
“…Named “Brilliant Joy in a Box,” the program was based on our previous research on joy (i.e., an emotion to support positive relationship development with the purpose of sustaining bonds and preparing children to face adversity; (Belsky et al, 1991; Fredrickson, 2004) and positive parenting practices, as well as ethnic-racial identity development among Black youth. We previously demonstrated that Black mothers taught their children to cope with frustrating situations in the future through joy and “freedom dreaming” (Mims et al, 2022), and that the messages parents conveyed about race in addition to how the child interpreted those messages in relation to their own identities were an important avenue for learning (Bocknek et al, 2020; Duane et al, 2020; Mims et al, 2022). We also found that positive parenting processes were not distinctly altered by systemic and external stress such as economic adversity or maternal psychopathology (Bocknek et al, 2020).…”
Section: Introductionmentioning
confidence: 99%